Existence of Positive Solutions of a Singular Nonlinear Boundary Value Problem. (18th August 2010) - Ma, Ruyun; Li, Jiemei
Abstract : We are concerned with the existence of positive solutions of singular second-order boundary value problemu ″ ( t ) + f ( t, u ( t ) ) = 0, t ∈ ( 0, 1 ), u ( 0 ) = u ( 1 ) = 0, which is not necessarily linearizable. Here, nonlinearityf is allowed to have singularities att = 0, 1 . The proof of our main result is based upon topological degree theory and global bifurcation techniques.